Strengthening of the surface of steel (9XФМ) exposed to a high-current electron beam - Prokhorenko, E.M.; Lytvynenko, V.V.; Melyakovа, O.А.; Lonin, Yu.F.; Ponomarev, A.G.; Uvarov, V.T.; Shulgin, N.A.; Prokhorenko, T.G.; Starovoytov, R.I.; Morozov, A.I.; Artemev, S.R. (Вопросы атомной науки и техники, 2020)
9ХФМ steel was irradiated with a high-current electron beam. The high-current electron beam was obtained in the TEMP-A accelerator. The irradiation was performed for various samples of the material of a ball mill drum. Part of the samples were taken from the surface of the balls, which had different degrees of wear. Samples taken from the depth of the balls, which is equal to half the diameter, were also irradiated. Microhardness measurements, metallographic, and fractographic analysis were used to study mechanical and microstructural changes. In all cases, a change in hardness was detected. The degree of change in hardness is different for different samples. Based on fractographic analysis, using SEM microscopy, one of the mechanisms that contribute to increasing the surface hardness is determined. This mechanism is the cleaning of the surface of samples from impurities of phosphorus and sulfur using a high-current electron beam. Сталь 9ХФМ була опромінена сильнострумовим електронним пучком, який отримано в прискорювачі ТЕМП-А. Опромінення проводили для різних зразків матеріалу кулі барабанного млина. Частина зразків була взята з поверхонь куль, які мали різний ступінь зносу. Також опромінювали зразки, узяті з глибини куль, яка була рівна половині діаметра. Для вивчення механічних і мікроструктурних змін застосовували виміри мікротвердості, металографічний і фрактографічний аналізи. У всіх випадках виявлена зміна твердості та пластичності. Для різних зразків ступінь зміни твердості та пластичності різна. На основі фрактогрaфічного аналізу з використанням РЕМ-мікроскопії визначений один з механізмів, який сприяє підвищенню твердості поверхні. Цим механізмом є очищення поверхні зразків за допомогою сильнострумового пучка електронів від домішок фосфору і сірки. Сталь 9ХФМ была облучена сильноточным электронным пучком, который получен в ускорителе ТЕМПА. Облучение проводили для различных образцов материала шара барабанной мельницы. Часть образцов взята с поверхности шаров, которые имели различную степень износа. Также облучали образцы, взятые из глубины шаров, которая равна половине диаметра. Для изучения механических и микроструктурных изменений применяли измерения микротвердости, металлографический и фрактографический анализы. Во всех случаях обнаружено изменение твердости. Для различных образцов степень изменения твердости различна. На основе фрактогрaфического анализа с использованием РЭМ-микроскопии определен один из механизмов, который способствует повышению твердости поверхности. Этим механизмом является очистка поверхности образцов с помощью сильноточного пучка электронов от примесей фосфора и серы.